Mechanical Analysis and Structural Optimization of Anchorage for Split Segment Inserted Tooth Slips - Lv, Kaixin; Hu, Zhongzhi (International Journal of Mechanical and Electrical Engineering, 2025)
This study investigates the anchoring capacity issues pertaining to internally-fitted inserted tooth slips within 140-grade casing pipes. By conducting static analysis, a formula linking tooth stress to tooth diameter, tooth inclination angles (both frontal and rear), and the base inclination angle has been formulated. Utilizing orthogonal testing and finite element simulations, the structural parameters of segmented toothed slips were refined. The findings reveal that by setting the tooth diameter at 7mm, the base wedge angle at 18°, the tooth groove angle at 55°, the tooth height at 6.5mm, and the circumferential angle at 8°, there is a notable enhancement in the evenness of stress distribution between the teeth and casing, resulting in a more balanced anchoring effect.